New Patterns for Comparative Religion: Passages to an Evolutionary Perspective, by William E. Paden. - Andrews, Corey (International journal for the study of new religions, 2020)
New Patterns for Comparative Religion: Passages to an Evolutionary Perspective, by William E. Paden. Bloomsbury Academicc, 2017. 264pp., Hb. 135.00. ISBN-13: 9781474252102. Pb. $40.45. ISBN-13: 9781350057890. ePDF 32.36. ISBN-13: 9781474252119.